Massaria broussonetiae sp. nov. and M. racemosae sp. nov. (Massariaceae, Pleosporales) on moraceous hosts - Samarakoon, Milan C.; Liu, Jian-Kui; Karunarathna, Samantha C.; Mukjang, Nilita; Cheewangkoon, Ratchadawan (Phytotaxa, 2022)
Massaria species are well-known in temperate regions in contrast to tropical regions. Taxonomy and phylogeny of two new Massaria species are carried out in this study as a part of our major research interests in microfungal diversity and distribution in Asia. In 2018–2019, we collected two fungal collections similar to Massaria from China and Thailand. Based on distinct morphology, multigene phylogeny, and host data, we introduce two new species, Massaria broussonetiae on Broussonetia sp. and M. racemosae on Ficus racemosa. Full descriptions, colour photo plates and a phylogenetic tree to show the placement of new species are provided.